Comparison of posterior capsule opacification between a 1-piece and a 3-piece microincision intraocular lens. Issue 3 (5th September 2012) - Prinz, Ana; Vecsei-Marlovits, Pia Veronika; Sonderhof, Dietrich; Irsigler, Paul; Findl, Oliver; Weingessel, Birgit
Abstract : Objective: To compare the intensity of posterior capsular opacification (PCO) between a 1-piece and a 3-piece microincision cataract surgery intraocular lens (MICS IOL) in a prospective randomised study. Methods: 80 eyes of 40 patients with age-related cataract were enrolled in this study. Each patient received a 1-piece MICS IOL (AF-1 NY-60, Hoya, Tokyo, Japan) in one eye and a 3-piece MICS IOL (AF-1 iMICS Y-60H, Tokyo, Hoya) in the other eye. At the 1-year follow-up, the patients were examined at the slit lamp, visual acuity was determined and standardised high-resolution digital retroillumination images were taken for objective quantification of regeneratory PCO using an automated image analysis software (AQUA). Results: The mean regeneratory PCO score (1-piece IOL: 0.2, 3-piece IOL 0.3, p=0.7) and the neodymium:yttrium-aluminium-garnet laser capsulotomy rate (two cases in 3-piece IOL group; p=0.5) were comparable low for both IOLs. Capsular folds occurred significantly more often in the 3-piece IOL group (p=0.02). Conclusions: Modification of the MICS IOL from a 3-piece to a 1-piece haptic design caused in short term no significant change in PCO amount. Compared with the 3-piece IOL, the 1-piece IOL led to significantly less capsular folds 1 year after surgery.